Study of the Biological Developmental Characteristics of the Eye in Children After Laser Surgery for the Treatment of Retinopathy of Prematurity - Zeng, Xianlu; Chen, Miaohong; Zheng, Lei; Tian, Ruyin; Chen, Yi; He, Honghui; Zeng, Jian; He, Jicang; Zhang, Guoming (Frontiers in Medicine, 2022)
Objective To observe the differences in ocular biology between premature infants who had undergone retinal laser photocoagulation (LP) for retinopathy of prematurity (ROP) and full-term infants and to investigate the relationships between these differences and the development of the refractive state. Methods This retrospective, cross-sectional study included 25 children (50 eyes) who had undergone laser treatment for aggressive posterior retinopathy of prematurity (AP-ROP), ROP in zone I requiring treatment, or ROP in zone II requiring treatment in the posterior pole (laser group) and 29 full-term infants (58 eyes) who had not (control group). Basic information, spherical equivalent (SE), and best corrected visual acuity (BCVA) were collected from the two groups. Their mean ages were 7.32 ± 2.85 and 7.34 ± 2.57 years, respectively (t = −0.047, P = 0.96). Ocular biology data were measured using an IOL Master 700 instrument (Carl Zeiss Meditec AG) and the data were processed using MATLAB (R2016a, Mathworks Inc.). The data markers included central corneal thickness (CCT), anterior and posterior surface corneal curvature radius (CCR), anterior chamber depth (ACD), lens thickness (LT), lens anterior surface curvature radius, lens posterior surface curvature radius, and eye axis length (AL). Optometric data were collected simultaneously and all BCVA values were converted to the logarithm of the minimum angle of resolution (LogMAR) for analysis. The data were statistically analyzed using SPSS software (V.23.0). Independent sample t-tests were used for the assessment of ocular biology and refractive indices in both groups of children and Pearson correlation coefficients were used to evaluate the correlations between age, gestational age at birth and ocular biology structural parameters. P < 0.05 was considered statistically significant. Results Comparisons of ocular biomarkers, refractive status, and BCVA between children in the laser and control groups showed relationships among ocular biomarkers, including the corneal-related parameters of CCT (0.54 ± 0.04 mm and 0.56 ± 0.03 mm, t = −2.116, P < 0.05), anterior surface CCR (7.53 ± 0.33 mm and 7.84 ± 0.30 mm, t = −5.063, P < 0.05), posterior surface CCR (6.75 ± 0.34 mm and 7.03 ± 0.24 mm, t = −4.864, P < 0.05); as well as those related to anterior chamber depth (ACD) were 3.24 ± 0.26 mm and 3.64 ± 0.26 mm, respectively (t = −8.065, P < 0.05), lens-related parameters (LT) were 3.80 ± 0.19 mm and 3.45 ± 0.16 mm, respectively (t = 10.514, P < 0.05); anterior lens surface curvature radius were 10.02 ± 0.93 mm and 10.52 ± 0.85 mm, respectively (t = −2.962, P < 0.05); posterior lens surface curvature radius were 5.55 ± 0.51 mm and 5.80 ± 0.36 mm, respectively (t = −2.917, P < 0.05), and ocular axis (AL) were 22.60 ± 1.42 mm and 23.45 ± 1.23 mm, respectively (t = −3.332, P < 0.05). Moreover, comparison of refractive status and BCVA between two groups of children showed an SE of −1.23 ± 3.38 D and −0.07 ± 2.00 D (t = −2.206, P < 0.05) and LogMAR (BCVA) of 0.12 ± 0.13 and 0.05 ± 0.11 (t = 3.070, P < 0.05). Analysis of the correlations between age and ocular biomarkers and refractive status of children in the laser and control groups showed correlations between age and ocular biomarkers in the two groups, in which age in the laser group was positively correlated with AL (r = 0.625, P < 0.05) but not with other biomarkers (P > 0.05). Age in the control group was negatively correlated with CCT, ACD, and AL (r = 0.303, 0.468, 0.703, P < 0.05), as well as with LT (r = −0.555, P < 0.05), with no correlation with other biomarkers (P > 0.05). Analysis of the correlation between age and refractive status of children in both groups showed that the age of children in both laser and control groups was negatively correlated with SE (r = −0.528, −0.655, P < 0.05) and LogMAR (BCVA) (r = −0.538, −0.542, P < 0.05). Analysis of the correlations between refractive status and ocular biomarkers in children in the laser and control groups showed that the refractive status in children in the laser group was negatively correlated with AL (r = −0.773, P < 0.05) but not with other biomarkers in this group (P > 0.05). The refractive status of children in the control group was negatively correlated with ACD and AL (r = −0.469, −0.734, P < 0.05), positively correlated with LT (r = 0.364, P < 0.05), and was not correlated with other biomarkers in this group (P > 0.05). Analysis of the correlations of gestational age at birth with ocular biomarkers and refractive status in children in the laser group showed a positive correlation between gestational age at birth and AL (r = 0.435, P < 0.05) but no other correlations with the other biomarkers (P > 0.05). Moreover, gestational age at birth was negatively correlated with SE (r = −0.334, P < 0.05) and LogMAR (BCVA) (r = −0.307, P < 0.05) in children in the laser group. Conclusions Compared to full-term infants, the development of CCT, ACD, LT, and AL was relatively delayed after ROP laser surgery, resulting in thin central corneal thickness, steep corneas, shallow anterior chambers, thicker lenses, “rounder” lens morphology, increased refractive power, and short eye axes, leading to the development of myopia. The changes in refractive status were mainly influenced by increased lens thickness. The results of this study showed that the lower the gestational age at birth, the greater the effects on emmetropization in children after ROP, and the more likely the development of myopia.